Implications of Entrepreneurship Education as a Field of Study for Advancing Research and Practice - Agustian Zen; Ratih Kusumastuti; Diksi Metris; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat (Journal on Education, 2023)
Entrepreneurship education is very important theoretically, but also practically. Thus, it is interpolated into university study programmes. In this study, we will explore how the implications of entrepreneurship education as a field of study for the advancement of research and practice. To do this, we draw on entrepreneurship education practices that have been analysed by previous researchers. This reflection will enable a better understanding of the current state of entrepreneurship education theory and practice. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study show that entrepreneurship education into a study programme does not only teach students futuristic thinking, but real action. Students need to know how classroom learning can inspire entrepreneurial practice. This condition has theoretical and practical consequences because it can demonstrate the purpose of entrepreneurship education which is job creation. Entrepreneurship education is very important because entrepreneurs should have a great social impact. This situation is influenced as well as affecting the cognitive, affective, and behavioural studies of entrepreneurship theory.